A reappraisal of inspiratory capacity in chronic obstructive pulmonary disease: clinical correlates and role of long-acting muscarinic antagonists and long-acting β2 agonists. Issue 6 (3rd June 2022) - Danzo, Fiammetta; Radovanovic, Dejan; Gatti, Marina; Saad, Marina; Perotto, Luca; Franceschi, Elisa; Santus, Pierachille
ABSTRACT: Introduction: In patients with chronic obstructive pulmonary disease (COPD), static and dynamic hyperinflation, together with expiratory flow limitation and gas exchange abnormalities, is one of the major causes of dyspnea, decreased exercise performance and ventilatory failure. An increase in functional residual capacity (FRC) is accompanied by a decrease in inspiratory capacity (IC), which is a volume readily available, repeatable, and simple to measure with any spirometer. Changes in IC and FRC after bronchodilation, contrary to changes in FEV1, have been closely associated with improvements in dyspnea and exercise performance. We systematically searched PubMed and Embase databases for clinical trials that assessed the effects of dual bronchodilation on inspiratory capacity in patients with COPD. Areas covered: Despite their pivotal role in COPD, IC and static volumes have rarely been considered as primary outcomes in randomized clinical trials assessing the efficacy of bronchodilators. Available studies on dual bronchodilation have shown a significant and persistent positive impact on IC focusing mainly on patients with moderate-to-severe COPD, whereas dynamic hyperinflation is also present at milder disease stages. Expert opinion: This narrative review discusses the pathophysiological and clinical importance of measuring IC in patients with COPD and how IC can be modified by maximizing bronchodilation combining long-acting muscarinic antagonists and long-acting β2 agonists.